2020
DOI: 10.1017/nws.2020.1
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional similarity in multiplex networks: friendships between same- and cross-gender bullies and same- and cross-gender victims

Abstract: Similar peers are more likely to become friends, but it remains unclear how the combination of multiple characteristics, known as multidimensional similarity, influences friendships. This study aimed to investigate whether similarity in gender (attribute) and bullying or victimization (network position) contributes to friendships. The school-level networks of friendships and victim-bully relationships in 17 Dutch elementary schools (2,130 students) were examined using multiplex longitudinal social network mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…Furthermore, recent work suggests the utility of using SAOMs to examine the role of multiplex relationships in peer selection and influence processes. For example, selection and influence processes related to peer victimization may depend on multiplex dynamics between dyadic bullying and defending relationships (Huitsing et al, 2014) or between dyadic victim-bully relationships and friendships (Hooijsma et al, 2020;Rambaran et al, 2020). Furthermore, because most SAOM studies focus on positive relationships like friendship, future research should examine the role of negative relationships, such as dyadic victim-bully relationships, in selection and influence processes related to internalizing behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent work suggests the utility of using SAOMs to examine the role of multiplex relationships in peer selection and influence processes. For example, selection and influence processes related to peer victimization may depend on multiplex dynamics between dyadic bullying and defending relationships (Huitsing et al, 2014) or between dyadic victim-bully relationships and friendships (Hooijsma et al, 2020;Rambaran et al, 2020). Furthermore, because most SAOM studies focus on positive relationships like friendship, future research should examine the role of negative relationships, such as dyadic victim-bully relationships, in selection and influence processes related to internalizing behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies limited the nominations ranging from a low of three nominations to a high of twenty nominations (Lodder et al, 2016). Other studies, including research using the Dutch KiVa dataset (Hooijsma et al, 2020;Huitsing et al, 2014;Rambaran et al, 2020), allowed for unlimited nominations. The response rates in most studies were 80% or higher in each network, but other studies reported lower response rates for some networks Sentse et al, 2013;Sijtsema et al, 2013).…”
Section: Peer Victimizationmentioning
confidence: 99%
“…An explanation is that "defenders of bullies" assisted bullies first, but then are influenced to turn their aggression also to the victims (Figure 11.3.b → Figure 11.3.c). A recent study documented that the friendships between bullies were more likely for same-sex than for crosssex bullies (Hooijsma et al, 2020). Other studies on negative relations (general dislike: "Who do you dislike") also found evidence for influence effects, suggesting that, over time, friends 13 had a tendency to agree about whom to dislike (Berger & Dijkstra, 2013;Pál, Stadtfeld, Grow, & Takács, 2016;Rambaran, Dijkstra, Munniksma, & Cillessen, 2015).…”
Section: New Directions In Social Network Dynamics In Bullying and Victimizationmentioning
confidence: 96%
“…An explanation is that "defenders of bullies" assisted bullies first, but then are influenced to turn their aggression also to the victims (Figure 11.3.b → Figure 11.3.c). A recent study documented that the friendships between bullies were more likely for same-sex than for crosssex bullies (Hooijsma et al, 2020). Other studies on negative relations (general dislike: "Who do you dislike") also found evidence for influence effects, suggesting that, over time, friends had a tendency to agree about whom to dislike (Berger & Dijkstra, 2013;Pál, Stadtfeld, Grow, & Takács, 2016;Rambaran, Dijkstra, Munniksma, & Cillessen, 2015).…”
Section: New Directions In Social Network Dynamics In Bullying and Victimizationmentioning
confidence: 97%